Dynamics in the Creative Sector between Rome and the Sea - Lelo, Keti (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
Over the last fifty years the tendency towards a dispersion of productive activities that emerged with globalisation and the advent of telematics have fuelled processes that are changing the structure of metropolitan areas across the world. Against the background of the general process of metropolisation, it is interesting nowadays to study the characteristics, structure and development trends of a vast “hybrid” area that has grown up around the established city of Rome. The subject of this work is an analysis of the creative sector between Rome and the sea, and the potential for future development in this area.